Conservation Reserve Program: Overview and Discussion - Juhyan Oh; Zhengfei Guan (EDIS, 2016)
The Conservation Reserve Program, a governmental initiative with the goal of protecting the environment by retiring less productive but environmentally sensitive cropland from production, is by far the largest-scale, biggest-budgeted conservation program in the United States. The program has been a success, improving the land allocation of primary crop production and providing environmental benefits, but it is currently confronted with government budget cuts, and some farmers are reluctant to participate. This 5-page fact sheet provides an overview of the Conservation Reserve Program and discusses relevant issues for Florida. Written by Juhyun Oh and Zhengfei Guan, and published by the Food and Resource Economics Department, November 2015.